Mechanical and Durability Properties of Concrete Made with Used Foundry Sand as Fine Aggregate. (30th September 2015) - Ganesh Prabhu, G.; Bang, Jin Wook; Lee, Byung Jae; Hyun, Jung Hwan; Kim, Yun Yong
Abstract : In recent years, the construction industry has been faced with a decline in the availability of natural sand due to the growth of the industry. On the other hand, the metal casting industries are being forced to find ways to safely dispose of waste foundry sand (FS). With the aim of resolving both of these issues, an investigation was carried out on the reuse of waste FS as an alternative material to natural sand in concrete production, satisfied with relevant international standards. The physical and chemical properties of the FS were addressed. The influence of FS on the behaviour of concrete was evaluated through strength and durability properties. The test results revealed that compared to the concrete mixtures with a substitution rate of 30%, the control mixture had a strength value that was only 6.3% higher, and this enhancement is not particularly high. In a similar manner, the durability properties of the concrete mixtures containing FS up to 30% were relatively close to those of control mixture. From the test results, it is suggested that FS with a substitution rate of up to 30% can be effectively used in concrete production without affecting the strength and durability properties of the concrete.